2002
DOI: 10.1021/jp0127566
|View full text |Cite
|
Sign up to set email alerts
|

Distance Dependence of the Electric Field Effect on Photoinduced Electron Tunneling between Cyanine Dye and Viologen through a Fatty Acid Monolayer

Abstract: Distance dependence of the electric field effect on the interlayer photoinduced electron tunneling from cyanine dye to viologen through a fatty acid has been examined using various spacer layers of fatty acid, based on the fluorescence measurements. The magnitude of the field-induced change in tunneling rate is shown to increase monotonically with decreasing the donor-acceptor distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…These values of β are still, however, within values quoted for other systems, although these are for saturated systems. For example, Ohta et al reported a β value of 0.23 Å −1 (equivalent to 0.3 per -CH 2 -) for electron tunneling from cyanine dye to viologen through a fatty acid, and in DNA systems values between 1.4 and 0.1 Å −1 (1.8 and 0.13 per methylene group) have been reported for double strands, while Vanmaekelbergh and co-workers , have quoted β-values of 0.5 Å −1 (0.6 per -CH 2 -) for CdSe quantum dots linked to gold surfaces by nonsaturated dithiols. However, very recently β values have been quoted of 0.69 Å −1 (0.88 per -CH 2 -) for 4-nm gold particles and 0.40 Å −1 (0.51 per -CH 2 -) for 2-nm gold particles …”
Section: Resultsmentioning
confidence: 99%
“…These values of β are still, however, within values quoted for other systems, although these are for saturated systems. For example, Ohta et al reported a β value of 0.23 Å −1 (equivalent to 0.3 per -CH 2 -) for electron tunneling from cyanine dye to viologen through a fatty acid, and in DNA systems values between 1.4 and 0.1 Å −1 (1.8 and 0.13 per methylene group) have been reported for double strands, while Vanmaekelbergh and co-workers , have quoted β-values of 0.5 Å −1 (0.6 per -CH 2 -) for CdSe quantum dots linked to gold surfaces by nonsaturated dithiols. However, very recently β values have been quoted of 0.69 Å −1 (0.88 per -CH 2 -) for 4-nm gold particles and 0.40 Å −1 (0.51 per -CH 2 -) for 2-nm gold particles …”
Section: Resultsmentioning
confidence: 99%
“…Values of ket estimated here show an effective linearity in retarding the electron transfer upon increasing the PCBM concentration. As reported, [ 27,38 ] the effect of an electric field on the rate of photoinduced electron transfer depends strongly on the donor‐acceptor distance. Even in the same pair of donor and acceptor molecules, electron transfer was theoretically shown to be accelerated and decelerated on application of an electric field, depending on the donor‐acceptor distance.…”
Section: Resultsmentioning
confidence: 93%